Developing solution scheme to grade online student's workout answer on linear algebraic equation / Khairul Nurmazianna Ismail - Ismail, Khairul Nurmazianna (Faculty of Computer and Mathematical Sciences, 2007)
Nowadays most applications are carried out using Information Technology (IT). Through efficient electronic networking system such as Internet, people are able to communicate and interact actively and efficiently in term of time. Through IT, learning and teaching is now done rather effectively via electronically. This project discusses to provide an online evaluating on student via web page by developing a program/engine by using string similarity method in evaluating electronic answers on algebraic equations that are submitted by the students through online. In the system, solution for algebraic question issues by lecturer will be generated automatically to make it efficiently. There are several experiments carried out to generate the solutions. Firstly, experiment using algebraic rules is explained. In this technique, lecturers need to input the algebraic question only. Problem using this technique is only one known algebraic laws is used that is distributive law. Secondly, permutation technique is used to increase the number of solutions. Permutation is about rearrangement of objects or symbols into distinguishable sequences. Problem using this technique is that meaning of the equation change. Finally combination of Right Hand Side to Left Hand Side, Left Hand Side to Right Hand Side and Switch Side are used. Scheme 1 is use to expand the generated solution scheme.